Character Strengths: Person–Environment Fit and Relationships With Job and Life Satisfaction - Gander, Fabian; Hofmann, Jennifer; Ruch, Willibald (Frontiers in Psychology, 2020)
Several studies demonstrated the relevance of character strengths in the workplace. For example, it has been shown that they positively relate to performance and are strong predictors of job satisfaction. Further, it was demonstrated that occupational groups differ in their average levels of character strengths. However, little is known about the effects of the congruence between a person’s strengths profile with the average profile within an occupational type (environmental congruence) on well-being. In a nationally representative sample (N = 870) of employed adults, we analyzed data on character strengths (t1), and measures of job and life satisfaction at three different time points (t1-t3; separated by one year). We studied (1) whether employees in different occupational groups differ with regard to their levels and configurations of character strengths; (2) how levels and configurations of character strengths relate to concurrent and predictive job and life satisfaction; and (3) whether a fit between strengths of a person and the environment goes along with current and future job and life satisfaction. Results confirmed previous findings that small, but meaningful differences in character strengths among employees in different occupational groups can be found and that character strengths positively relate to current and prospective job and life satisfaction. Further, results suggested that a better person-environment-fit goes along with higher job and life satisfaction. These results suggest character strengths could play an important role in vocational and career counseling.